(untitled) - MELADIYA, HIKMA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
The burgeoning various types of business in the culinary field, means competitions is going on between the culinary business will be more stringent. Changes in lifestyle, habits, and manner of tastes to enjoy and consume foodin urban communities make the culinary business doing things that can affect consumers that the consumer decides to buy yhe products offered top. The current atmosphere is an important factor for consumers in choosing dining. Comfortable atmosphere with unique and creative decorating the main attraction for a restaurant that makes consumers need to visit the restaurant. Layou (X1), odor (X2), physical appereance (X3) and design of the building (X4) in Mc Donald’s F obtained by count 64,492 and T count for 3,636 with a significance level of less than 0,05 then concluded the influence simultaneously and partially between layout, odor, physical appereance, and design of the building on purchasing decisions. Keyword : store atmosphere, layout, odor, physical appereance, design of the building, purchasing decision.